A qualitative analysis of interactive performer-audience methods with specific reference to Interactive Themba Theatre (ITT) - James, Inge (My University, 2009)
Abstract The investigation of theatre as an agent of transformation raises the question of how this is possible. Theatre’s most notable attribute is its ability to engage the hearts and minds of its audience members. The central argument that people make decisions through a rational and emotional process correspondingly, positions theatre as a possible channel of influence on its audience members. Applied Theatre for HIV/AIDS education provides a platform for further exploration of the possible impact theatre has on the behaviour of its audiences, with specific reference to Interactive Themba Theatre (ITT) and adolescents. This study commences with reference to the potential of Interactive Theatre in Chapter One as a medium for experiential learning through active participation – complying with the documented prerequisites for effective learning. Chapter Two gives a brief overview of the development of revolutionary theatre forms utilising interactive approaches, and concludes with specific focus on Theatre In Education (TIE) and its key features. Chapter Three presents semiotics as a theoretical research methodology which enables interpretive observations of the ITT process, together with qualitative assessment criteria primarily based on engagement levels of audience members. These form a proposed framework for analysis of interactive performer-audience methods. Chapter Four focuses on Interactive Themba Theatre (ITT) as a case study and presents the ITT methodology, its approach to learning, and performance processes. Chapter Four also introduces the respective schools where observations took place. Chapter Five gives descriptive observations of the ITT process, specifically referring to the elements within preparation, presentation and post-performance encounters, with a central focus on the engagement levels of learners during the ITT process. Chapter Six analyses the observations made in Chapter Five in relation to the theatre group’s fulfilment of their prescribed aims and objectives, with specific reference to the elements within the preparation, presentation and post-performance encounters. This chapter looks at prescribed objectives in relation to actual outcomes, and will focus on engagement of the interactive performer-audience methods with the purpose of investigating their efficacy as a medium for audience interaction. Chapter Seven comprises recommendations of the investigations to enhance the interactive theatre process relating to the preparation, presentation and postperformance dynamics in a TIE programme. The conclusion in Chapter Eight highlights the importance of engagement in the interactive methods of a TIE programme for optimum impact to occur. It also highlights that while learning may play a significant role in influencing behaviour, it may not necessarily result in behavioural change. In this regard, it is indicated how further engagement at an affective level might impact audiences to the extent that behaviour may be influenced.